Nitrogen‐Doped Ordered Mesoporous Anatase TiO2 Nanofibers as Anode Materials for High Performance Sodium‐Ion Batteries. Issue 26 (17th May 2016) - Wu, Ying; Liu, Xiaowu; Yang, Zhenzhong; Gu, Lin; Yu, Yan
Abstract : Nitrogen‐doped ordered mesoporous TiO2 nanofibers (N‐MTO) have been fabricated by electrospinning and subsequent nitridation treatment. The N‐doping in TiO2 leads to the formation of Ti 3+, resulting in the improved electron conductivity of TiO2 . In addition, one‐dimensional (1D) N‐MTO nanostructure possesses very short diffusion length of Na + /e − in N‐MTO, easy access of electrolyte, and high conductivity transport of electrons along the percolating fibers. The N‐MTO shows excellent sodium storage performance.